Identity capital and graduate employment: an investigation into how access to various forms of identity capital relates to graduate employment - Kiley, Jerome (School of Management Studies, 2021)
Students at higher education institutions expect that their investment in education will be rewarded through positive employment outcomes. The dearth of research into graduates' personal circumstances which contribute to whether these expectations translate into reality was the starting point for this PhD thesis. Specifically, the thesis considered the role of identity development for success in the employment search. Erikson's and Arnett's theories of identity development and Côté's identity capital model were used as the theoretical basis to develop the Identity Capital Model of Graduate Employment (ICMGE). Erikson and Arnett proposed that gaining meaningful employment is a crucial task in an individual's development trajectory when moving from adolescence into adulthood. Côté's model explains under what condition this transition is likely to be successful: Individuals with greater access to resources, both tangible and intangible, are more agentic and thus in a better position to deal with identity formation challenges. The ICMGE thus proposed that graduates with more intangible identity capital, i.e. greater agentic personality, and greater access to tangible identity resources in the form of financial, human, social and cultural capital are more employable, which reflected in a greater chance of finding employment, a shorter time to find employment and higher quality employment. Given that in the South African context historically members of different racial and gender groups had unequal access to employment opportunities for which current employment legislation seeks to provide redress, race and gender were included as additional predictors of graduate employment. To test the ICMGE empirically, students' identity capital, race and gender were assessed via quantitative surveys, with data collected from N = 872 students in their final year of study at different higher education institutions in the Western Cape Province of South Africa. A year later, N = 508 of these participants provided data about their current employment situation in telephonic interviews. Contrary to expectations, not all forms of identity capital were related to one another. The strongest correlations emerged between financial and human capital, with weaker correlations with cultural capital. Social and psychological capital generally did not correlate significantly with other forms of identity capital. The level of identity capital differed by race, but no gender differences emerged. The ICMGE successfully predicted employment amongst 81.9% of the respondents. However, only race and cultural capital, in the form of type of secondary school and type of tertiary institution attended, and home language explained unique variance in the probability of gaining employment. Those who had attended former Model C or private schools, higher status tertiary institutions, were English speakers, and self-identified as white or coloured had a greater probability of gaining employment. Greater social capital, measured by the number of extracurricular activities participated in, was related to a lower probability of being employed. It is likely though that the indicator used for social capital was not appropriate, given that close to half of the employed respondents indicated having secured employment through social contacts. The quality of employment obtained was mostly predicted by race and agentic personality. Those who were more agentic in their approach to life, and those who identified as either white or coloured, had obtained higher quality employment. Financial capital and home language were the most relevant predictors of the time taken to gain employment. Those with greater financial capital and English or Afrikaans speakers spent longer looking for employment. Academic grades had little relevance in predicting whether or not graduates obtained employment. The study adds new knowledge to the graduate employability literature in that it shows that a theoretically derived graduate employability model can be applied to real-world conditions by predicting actual employment rather than a graduate's employment potential. The study also demonstrated the value of considering graduates' identity development and access to identity capital when considering their chances to secure employment, and in particular the quality of this employment. The ICMGE model only predicted small amounts of the variance in the employment variables, however. It is thus recommended that future research make use of instruments that are more sensitive to the intricacies of the different types of capital in larger and more representative samples.